POPULATION GROWTH AND LITERACY RATE IN PATNA DISTRICT: A COMPARATIVE STUDY - Kumar, Birendra; Rautela, Poonam (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Population growth is a natural phenomenon but its explosion creates a big problem in the whole country. The socio-economic condition of a country depends on the human resource of that country. Because the development of a nation is measured by the total population gross income rate of the whole country. Education is the main means to shape the human resource in a proper way which shapes the human ability to earn and live a happy life. It is education that takes the nation in the right direction and helps in developing the overall condition of the country. In today's society, without education, we cannot think about the welfare of an individual as well as the whole country. So population growth and literacy rate are interdependent. If literacy rate increases then population will be controlled. Because educated people are aware about the harmful effects of over population or population explosion. Population explosion in Patna district is a big problem for the development of the state. The researcher tries to investigate the population growth and literacy rate of Patna district and its consequences. The study tries to find out the effect of literacy on controlling the population of Patna district. The study found that the increase in literacy rate is effective for controlling the population and welfare of the district and state. Because education is the only weapon to destroy the evil things from the society.